2014
DOI: 10.12697/smp.2014.1.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The Accentual Structure of Estonian Syllabic-Accentual Iambic Tetrameter

Abstract: Abstract. This paper is part of a project aimed to analyse the rhythm of Estonian binary verse metres. It is the first complex analysis of Estonian syllabic-accentual iamb. The analysis is comprised of poetry by 20 prominent authors from the end of the 19th century and the beginning of the 20th century, and, all in all, more than 9000 verse lines. In order to find out which regularities are specific to poetry in general or to a particular poet, these data were compared with pseudoiambic segments extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In verse culture it meant, first, the dramatic increase of different metrical and stanzaic forms, while at the same time the possibilities of quantitative verse were discovered and experimented with in various verse forms. Second, in the already established forms, new ways of expression and breaking the monotony were sought out (Lotman, Lotman 2013, 2014. The horizon was broadened, and in looking for new modes of expression the orientations shifted from the German tradition, first of all, to French and Russian poetic culture.…”
mentioning
confidence: 99%
“…In verse culture it meant, first, the dramatic increase of different metrical and stanzaic forms, while at the same time the possibilities of quantitative verse were discovered and experimented with in various verse forms. Second, in the already established forms, new ways of expression and breaking the monotony were sought out (Lotman, Lotman 2013, 2014. The horizon was broadened, and in looking for new modes of expression the orientations shifted from the German tradition, first of all, to French and Russian poetic culture.…”
mentioning
confidence: 99%
“…Similar investigations into English and Czech verse did not bring similar results: the picture is far more diversified. A multi-aspect study of Estonian iambic and trochaic tetrameter (Lotman & Lotman 2013, 2014, in which both the accentual and the quantitative structures of verse have been examined, and a gradual scale has been used (five grades of accent and three grades of duration), has demonstrated that the Estonian poetic tradition may be described as placed somewhere in the middle between the opposite types of evolution. On the one hand, the generalised accentual profile of the two metres shows no differences between authors, movements or periods.…”
mentioning
confidence: 99%